Identification of humoral immune indicators in some clinical manifestations in patients with heroin use disorder without hepatitis C infection - Simonovska, Natasha; Zafirova Ivanovska, Beti (My University, 2019)
Background: The effect of opioids on the immune system is a complex phenomenon dependent on such variables as the type of opioid, the character of the response (humoral versus cellular) and the types of cells involved. Aim: To characterize humoral immune indicators and determine their predictive impact on the onset of common clinical manifestations observed in heroin users without hepatitis C infection. Methods: A total of 140 outpatients were enrolled in this crosssectional study, which lasted over a 3.5-year period at the University Clinic of Toxicology in Skopje from January 2009 to June 2012. Multivariate logistic regression analysis was used to determine the impact of several humoral immune indicators at the onset of the common clinical manifestations. The following instruments were used for analysis of patient samples: immunoturbidimetric assay, indirect immunofluorescence, spectrophotometer, fluorescence polarization immunoassay. Results: Most of the patients were male n=108, with an average age of 28.34 ± 5.34 years. Arthralgia was observed in 42.14%, skin changes in 12.14%, respiratory difficulties in 15.0%, neurological disorders in 12.86%, Raynaud’s disease in 19.28%, and proteinuria in 42.86% of patients. Multivariate logistic regression analysis showed that significant factors having a potential correlation with intravenous heroin usage included: immunoglobulin G (0.027), immunoglobulin M (0.026), and cryoglobulins (<0.001). Conclusions: Heroin users with cryoglobulinemia have a greater chance of developing arthralgia, skin changes, respiratory difficulties, neurological disorders, and Raynaud’s disease. Some of these conditions were more common among participants who were taking heroin intravenously. These manifestations require treatment that is delivered on time.
Keywords: heroin use disorder; hepatitis C; virus negative; clinical manifestations; humoral immune indicators